2016
DOI: 10.1021/acs.jpcb.5b08398
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Thermal Conductivity of Graphene-Polyamide-6,6 Nanocomposites by Surface-Grafted Polymer Chains: Calculation with Molecular Dynamics and Effective-Medium Approximation

Abstract: By employing reverse nonequilibrium molecular dynamics simulations in a full atomistic resolution, the effect of surface-grafted chains on the thermal conductivity of graphene-polyamide-6.6 (PA) nanocomposites has been investigated. The interfacial thermal conductivity perpendicular to the graphene plane is proportional to the grafting density, while it first increases and then saturates with the grafting length. Meanwhile, the intrinsic in-plane thermal conductivity of graphene drops sharply as the grafting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 73 publications
0
44
0
Order By: Relevance
“…However, surface functionalization of 2D fillers does not always lead to a smaller interfacial thermal resistance. The effect of surface-grafted chains on the thermal conductivity of graphene@polyamide-6.6 nanocomposites has been studied using MD simulations [209]. It turns out that the thermal conductivity perpendicular to the graphene plane is proportional to the grafting density, while the in-plane thermal conductivity of graphene drops sharply as the grafting density increases.…”
Section: ) 2d Fillers (Graphene and Boron Nitride)mentioning
confidence: 99%
“…However, surface functionalization of 2D fillers does not always lead to a smaller interfacial thermal resistance. The effect of surface-grafted chains on the thermal conductivity of graphene@polyamide-6.6 nanocomposites has been studied using MD simulations [209]. It turns out that the thermal conductivity perpendicular to the graphene plane is proportional to the grafting density, while the in-plane thermal conductivity of graphene drops sharply as the grafting density increases.…”
Section: ) 2d Fillers (Graphene and Boron Nitride)mentioning
confidence: 99%
“…This may be due to the ultralow thermal conductivity of the polymer (~0.1 W/m·K) compared to that of graphene (>100 W/m·K), transforming the ballistic heat transfer in graphene to the diffusive heat transfer in polymers [76,77]. Moreover, a number of theoretical studies have demonstrated that the interfacial thermal resistance (often known as the Kapitza resistance) between graphene and polymer also lowers the thermal conductivity of the composite films [78][79][80][81].…”
Section: Hybridization With Other Componentsmentioning
confidence: 99%
“…However, excessive loading of grafted polymer may reduce the thermal conductivity of the graphene sheets, thus inducing lower effective thermal conductivity for the composite film. Therefore, the grafting density should be well-controlled to achieve a higher thermal conductivity of the composite film than the conductivity of the polymer matrix [81]. More discussion about nanoscale thermal transport based on phonon propagation can be found in other reviews [82,83].…”
Section: Hybridization With Other Componentsmentioning
confidence: 99%
“…The effect of chemical functionalization on thermal properties of junctions between nanoflakes was studied by MD calculations on a simplified model system, made of two adjacent graphene sheets edge functionalized with phenols or with the covalent molecular junctions ( Figure ), using a well‐known method previously reported. [12c]…”
Section: Resultsmentioning
confidence: 99%
“…To tailor the properties of nanopapers, the exploitation of molecular junctions between GRM nanoflakes is currently a promising possibility, yet experimentally challenging. In fact, while the conductance of molecular junctions was widely studied by molecular dynamics and density functional theory, the experimental exploitation of organic molecular junctions was only recently reported by Han et al for the thermal coupling of the graphene–graphene oxide and the graphene oxide–silica surfaces. In this work, both covalent and non‐covalent molecular junctions were designed and synthetized to create GRM‐based nanopapers with inherently low contact thermal resistance between nanoplatelets.…”
Section: Introductionmentioning
confidence: 99%